2000
DOI: 10.2214/ajr.175.1.1750239
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of CT-Guided Automated Needle Biopsy of Lung Nodules

Abstract: Lesion size was a determining factor in diagnostic accuracy. Diagnostic accuracy decreased in proportion to the decrease in the lesion diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
153
4
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(185 citation statements)
references
References 17 publications
18
153
4
6
Order By: Relevance
“…Most of the studies in the literature on CT guided FNaC have applied it to evaluate lung lesions (15)(16)(17)(18)(19). In our study as well, CT guided FNaC was performed only for lung lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies in the literature on CT guided FNaC have applied it to evaluate lung lesions (15)(16)(17)(18)(19). In our study as well, CT guided FNaC was performed only for lung lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of diagnostic accuracy have been documented between 72 and 100% for pulmonary metastatic lesions. However, the diagnostic accuracy decrease for smaller lesions between 10 and 20 mm; several studies have reported the diagnostic accuracy range of 52 and 96.5% [4,5].The purpose of our study was to review our experience with CT-guided biopsy of suspected LM with a view to providing a critical assessment of the efficacy and safety of the procedure.For reprint orders, please contact: reprints@futuremedicine.com …”
mentioning
confidence: 99%
“…The rates of diagnostic accuracy have been documented between 72 and 100% for pulmonary metastatic lesions. However, the diagnostic accuracy decrease for smaller lesions between 10 and 20 mm; several studies have reported the diagnostic accuracy range of 52 and 96.5% [4,5].…”
mentioning
confidence: 99%
“…El rendimiento global de la BP en este estudio fue de 91,5%, con una sensibilidad de 90,6% para el diagnóstico de lesiones malignas, resultados similares a los publicados en series internacionales [3][4][5][6] . La patología maligna fue la más común, siendo los tumores broncogénicos primarios y las lesiones metastásicas los diagnósticos más frecuentes, datos que concuerdan con casuísticas previas.…”
Section: Discussionunclassified
“…Algunas ventajas del método son su carácter no invasivo, baja tasa de complicaciones y menor costo 1,2 . El rendimiento reportado de la técnica fluctúa entre 83% y 99% en el caso de LP [3][4][5][6] . Yeow KM et al 6 , en una serie de 631 LP estudiadas con BP core guiada por TC, demostraron rendimientos de 99% para lesiones malignas y 86% para lesiones benignas, con un mejor rendimiento a mayor tamaño lesional (< 1,5 cm 84% y 1,5-5 cm 96%).…”
unclassified